Performance-Based Assessment in Assessing the Students’ Evaluating Skill: How is the implementation in English Learning? - Umniyyatul Makmuroh; Yusuf Olatunji Abimbowo; Samira Agoro (Educalingua, 2024)
Performance-based assessment (PBA) enables teachers to determine learners’ genuine language competency and promote critical thinking skills. The students applied their knowledge in practical ways during the teaching and learning process. Evaluating skill is one of the higher-order thinking abilities (HOTS) every individual should strive to master. Some research have indicated that this competence is under-evaluated. This study intends to elucidate the utilization of Performance-Based Assessment for evaluating students' skills in learning English. A qualitative research design was used to recruit an English teacher who met the study requirements and was teaching ninth-grade students at SMPN 2 Semarang. Information was collected through classroom observation, document analysis, and interviews. The study revealed that the teacher utilized probing questions in process-oriented assessment while applying performance-based assessment to evaluate students' skills in evaluating English acquisition. Challenging questions were asked during the learning activities to challenge students to think critically about their answers. The teacher led the pupils in a thorough discussion of the learning materials. The assessment questions were primarily open-ended WH questions designed to engage higher-order thinking skills